Evaluation of implementation effect of support for grassroots healthcare by nurse specialists of Traditional Chinese Medicine (中医护理专科团队下基层项目实施效果评价) - YAN Hong (颜红); ZHU Jinqing (朱进晴); WANG Huaxin (王华新); TANG Ling (唐玲) (中西医结合护理)
Beijing Administration of Traditional Chinese Medicine had carried out the Support Work for Grassroots Healthcare by Nurse Specialists of Traditional Chinese Medicine, in order to improve the skills of Traditional Chinese Medicine nursing team in health care and level of service in hospitals of traditional Chinese and Western medicine. This paper summarized the constructional method of the Support Project and its achievement, discussed the existing problems during the implementation, and laid foundation for the further research and practice. (为进一步提升中医护理队伍的服务能力, 提升转型中西医结合医院中医护理服务水平, 北京市中医管理局开展中医护理专科团队下基层工作。本文就项目建设的方法及成果进行总结, 并对实施过程中存在的问题进行探讨, 为进一步下基层帮扶、持续开展中医护理专家下基层项目奠定基础。)